The Adaptability of The Society in Dealing with The Vulnerability of Earthquake Threats in Bantul - Delfi Delfi (Policy & Governance Review, 2017)
Earthquake in Bantul on May 27, 2006 brought catastrophic impacts for society as the victims. There were the most serious damages and highest number of victims in Bawuran Village. On the other hand, Srigading Village had the lowest damages and there was no victim. Bawuran Village is located on graben which causes its vulnerability towards earthquake threat. Meanwhile, Srigading Village is situated on 3-10 meters above the sea level, which makes it vulnerable to tsunami. The adaptation capacity is very important to minimize the costs of natural disasters. Based on the reviews of those backgrounds, the researcher will examine the societal adaptation capacity in Bawuran and Srigading Village regarding to its vulnerability towards tsunami and earthquake. Societal adaptation capacity can be seen as society’s readiness in facing natural disasters. This research uses qualitative-descriptive method. Data collecting techniques are done by using literature study, field observation through interview and documentation. The researcher also has conducted an in-depth interview with the local government i.e. the oﬃcers of Regional Disaster Management Agency (BPBD) in Bantul Regency. The result of this research is to find out the society’s adaptation capacity towards earthquake, drought, landslide, flood, fallen tree, tornado and river flow closing in Bawuran Village. Meanwhile in Srigading Village, the risk of tsunami, flood and puddle have been found. The society’s adaptation capacity in Bawuran and Srigading Village can be assessed by using economic growth, social capital, information and communication, and social competence. Based on those assessments, societies do not have readiness in facing disasters yet. It is caused by poor economic condition, inadequate economic resources with low incomes in Bawuran Village, and the uneven population of Srigading Village. The networks within the community have not been fully developed. The community also cannot access information through the internet network. This is due to the unavailability of internet facilities in the two villages. It also lacks of disaster management competency. This condition is indicated by the absence of disaster programs in the two villages. Awareness from the society, especially the victims in responding disasters is also needed. The result of research shows that societies do not have readiness in facing any upcoming disasters yet.